2022
DOI: 10.37745/bje.2013/vol10n133344
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Subpar Academic Achievement of Public Basic Schools with Emphasis on Basic Education Certificate Examination (BECE): A Case Study of Sagnarigu Municipality in Northern Region, Ghana

Abstract: The study was set up to determine the causes of poor academic achievement in the Basic Education Certificate Examination (BECE) in the Sagnarigu Municipality in Tamale, Northern Region, Ghana. The study sought to identify the contributing causes of such subpar learning outcomes and to provide some policy interventions to address them. For the study, two research questions were established. Data collection and analysis were done using a qualitative approach. In relation to the basic schools in the Sagnarigu Mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…The World Bank further revealed a decline in the percentage of schools unaffected by teacher absences, which highly affected the achievement of learners. Saviour et al, (2022) revealed a correlation between students' subpar academic achievement and the inadequate performance of teachers. Sancassani's (2023) study agreed with Darling-Hammond (2000) which revealed a strong and positive correlation between teacher quality attributes, such as certification status and subjectspecific degrees and academic performance in the fields of science and mathematics.…”
Section: Teacher-side Factors That Influence Academic Performancementioning
confidence: 99%
“…The World Bank further revealed a decline in the percentage of schools unaffected by teacher absences, which highly affected the achievement of learners. Saviour et al, (2022) revealed a correlation between students' subpar academic achievement and the inadequate performance of teachers. Sancassani's (2023) study agreed with Darling-Hammond (2000) which revealed a strong and positive correlation between teacher quality attributes, such as certification status and subjectspecific degrees and academic performance in the fields of science and mathematics.…”
Section: Teacher-side Factors That Influence Academic Performancementioning
confidence: 99%